2009
DOI: 10.1093/cercor/bhp040
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Congruence during Cerebral Cortical Development

Abstract: There is evidence for interaction between the developing circulatory and nervous systems. Blood vessels provide a supporting niche in regions of adult neurogenesis. Here we present a systematic analysis of vascular development in the embryonic murine cortex and demonstrate that dividing cells, including Tbr2-positive intermediate progenitor cells, are closer to the vasculature than expected from a random distribution. To examine whether neurites of the newly generated embryonic neurons find blood vessels as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 29 publications
8
111
0
Order By: Relevance
“…It is well-known that in conventional neurogenic regions of the adult brain such as SVZ [58,59] and SGZ [4], NSPCs reside in vascular niches, and the vasculature is regarded as a key element throughout life. Although the niches for the cortical NSPCs in the adult brain remain unclear, our recent studies [15] and those of others [60,61] indicate that ECs are likely to be an important element of niches for NSPCs in the cerebral cortex. In support of this viewpoint, we have shown in the current study that proliferation of endogenous ischemia-induced NSPCs was observed more frequently near endogenous ECs in and around the poststroke cortex, and that the grafted ECs promoted the proliferation of endogenous NSPCs in that area.…”
Section: Discussionmentioning
confidence: 73%
“…It is well-known that in conventional neurogenic regions of the adult brain such as SVZ [58,59] and SGZ [4], NSPCs reside in vascular niches, and the vasculature is regarded as a key element throughout life. Although the niches for the cortical NSPCs in the adult brain remain unclear, our recent studies [15] and those of others [60,61] indicate that ECs are likely to be an important element of niches for NSPCs in the cerebral cortex. In support of this viewpoint, we have shown in the current study that proliferation of endogenous ischemia-induced NSPCs was observed more frequently near endogenous ECs in and around the poststroke cortex, and that the grafted ECs promoted the proliferation of endogenous NSPCs in that area.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, the comparisons of selected genes with known cortical VZ and SVZ expression in the mouse and opossum revealed very similar expression patterns. Even the SVZ‐specific vascular patterning was apparent (Stubbs et al, 2009; Cheung et al, 2010). These observations suggest that the smaller number of cortical neurons in the radial domain is associated with the reduction and late appearance of the SVZ in marsupials.…”
Section: Subventricular Zone In Sauropsids and Mammalsmentioning
confidence: 99%
“…In many organs, vascular and neural structures are closely aligned (Bearden and Segal, 2005;Correa and Segal, 2012;Mukouyama et al, 2005;Mukouyama et al, 2002;Stubbs et al, 2009), reflecting their interdependent existence (Quaegebeur et al, 2011) and synchronized function (Storkebaum and Carmeliet, 2011). Defining how these vascular and neural elements are patterned is important for a full understanding of organ formation, as well as pathological conditions.…”
Section: Introductionmentioning
confidence: 99%